Integrated Management of Arthropod Pests and Insect Borne Diseases - Ciancio, Aurelio; Mukerji, K.G.; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2010)
The fifth and last Volume of this IPMD series reviews, in a multi-disciplinary approach, recent achievements in crop protection and integrated management of arthropod pests. The volume is organized in a first section covering IPM in citrus productions, a Second one dealing with advancements in the integration of management technologies and a last section covering mites and their biological control agents. As for the previous volumes, we attempted to provide an informative coverage for a broad range of agricultural systems and situations. The chapters are mainly organized and centered on crops, with a particular emphasis on citrus. This is one of the main crops in which biological control and IPM approaches were tested successfully, and the experience gained herein may indeed result helpful for IMP efforts deployed worldwide on other crops and/or cropping systems. Chapters in Section 2 review the integration of insect and disease management options in pecan crops, the application of remote sensing technologies, the status of knowledge about plant defense compounds and their potentials. For IPM of invasive species, an update is provided on the experience gained on the Red Palm Weevil (RPW) in Egypt. Long-term technological solutions for IPM in forests and park areas through aerial treatments with Bt spores concludes this Section. Finally, in Section 3, updated reviews about biological control agents of mites are provided.
IPM IN CITRUS GROVES -- Citrus Pest Management in the Northern Mediterranean Basin (Spain, Italy and Greece) -- Main Arthropod Pests of Citrus Culture and Pest Management in Greece -- Biological Control in Citrus in Spain: From Classical to Conservation Biological Control -- Citrus Integrated Pest Management in Italy -- Entomopathogenic Nematode Ecology and Biological Control in Florida Citrus Orchards -- ADVANCED IPM TECHNOLOGIES -- Integration of Insect and Mite Management With Disease and Weed Control in Pecan Production -- Locust Habitat Monitoring and Risk Assessment Using Remote Sensing and GIS Technologies -- Plant Defenses Against Insect Herbivory -- IPM of the Red Palm Weevil, Rhynchophorus Ferrugineus -- Control of Urticating Lepidoptera Outbreaks With Bacillus Thuringiensis Aerial Treatments -- MITES BIOLOGICAL CONTROL AND IPM -- IPM Potentials of Microbial Pathogens and Diseases of Mites -- IPM Strategies Through Specialist and Generalist Phytoseiids (Acari, Mesostigmata).
Keywords: Life sciences; Agriculture; Botany; Plant diseases; Zoology; Entomology; Life Sciences; Plant Pathology; Entomology; Agriculture; Plant Sciences; Zoology